Comparison Analysis of Usability Using Controllers and Hand Tracking in Virtual Reality Gamelan (Sharon) Based On User Experience - Ardhika Wida Pangestu; Clara Hetty Primasari; Thomas Adi Purnomo Sidhi; Yohanes Priadi Wibisono; Djoko Budiyanto Setyohadi (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2022)
Gamelan is one of the traditional musical instruments in Indonesia. Gamelan is also one of the cultures that must be preserved. To preserve gamelan, one way is by combining gamelan with technology that is currently developing. The technology that is currently trending is virtual reality. Virtual reality is often used for games in three-dimensional form. Gamelan can be something interesting in VR. In VR interactions, there are two interactions that are often used, namely controllers and hand tracking. Hand gestures are usually tracked using the built-in camera of the VR. Hand tracking can be used in VR applications to control the virtual object just like a controllers. This study aims to compare the use of controllers and hand tracking that involve interactions, namely collision, pressing, grabbing, and release. Thirty two Atma Jaya Yogyakarta University students who had tried virtual reality and played gamelan or had seen gamelan performances explore the differences between VR hand tracking and VR controllers in VR gamelan sharon. SUS (System Usability Scale) and USEQ (Use Questionnaire) were used to measure user usability and satisfaction. The result of the SUS score showed that users were more interested in using controllers than hand tracking. But the USEQ results showed that there were no difference in usefulness, ease of use, and satisfication. Based on the results of the interaction, using controllers looked more comfortable, but using hand tracking, playing gamelan looked more realistic.